A cross-sectional study of sexual dysfunction in chinese mainland female patients with rheumatoid arthritis - Congcong ZHOU, (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the effects of rheumatoid arthritis (RA) on Chinese mainland female patients’ sexual function compared with healthy subjects and to determine the risk factors of sexual dysfunction. Patients and methods: A total of 151 female RA patients (mean age: 46.3±8.6 years) and 146 healthy female controls (mean age 45.7±7.6 years) were included in this cross-sectional study whose data were collected consecutively by questionnaires between November 2017 and June 2019. Data were collected by using demographics, disease-related information, Female Sexual Function Index, Dyadic Adjustment Scale, Medical Coping Modes Questionnaire, other psychological parameters and the Short Form-36. Results: Our results showed that the prevalence of female sexual dysfunction was 67.5% in RA patients, which was significantly higher than the controls (54.1%) (p<0.05). Body mass index, resignation coping style, physical component summary, marital dysfunction and postmenopausal status were significant correlation factors by backward stepwise binary logistic regression. Conclusion: Rheumatoid arthritis negatively affected sexual function of patients who had considerably impaired sexual function compared to controls.